2022
DOI: 10.1038/s41598-022-04939-z
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning assisted real-time deformability cytometry of CD34+ cells allows to identify patients with myelodysplastic syndromes

Abstract: Diagnosis of myelodysplastic syndrome (MDS) mainly relies on a manual assessment of the peripheral blood and bone marrow cell morphology. The WHO guidelines suggest a visual screening of 200 to 500 cells which inevitably turns the assessor blind to rare cell populations and leads to low reproducibility. Moreover, the human eye is not suited to detect shifts of cellular properties of entire populations. Hence, quantitative image analysis could improve the accuracy and reproducibility of MDS diagnosis. We used r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Such classification studies of whole cell deformation and shape have been done by others. [ 43–45 ] These studies demonstrated that analyzing multiple physical phenotype metrics together can be more accurate at classifying cancer cell lines than a single metric (e.g., stiffness) alone. Along these lines, the L‐EV stiffness measurements from non‐contact microfluidics could be an additional metric that contributes to the suite of EV characterizations used in the field to classify EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Such classification studies of whole cell deformation and shape have been done by others. [ 43–45 ] These studies demonstrated that analyzing multiple physical phenotype metrics together can be more accurate at classifying cancer cell lines than a single metric (e.g., stiffness) alone. Along these lines, the L‐EV stiffness measurements from non‐contact microfluidics could be an additional metric that contributes to the suite of EV characterizations used in the field to classify EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Such classification studies based on whole cell deformation and shape have been done by others. [41][42][43] These studies demonstrated that analyzing multiple physical phenotype metrics together can be more accurate at classifying cancer cell lines than a single metric (e.g., stiffness) alone.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly advantageous for probing complex spatiotemporal characteristics of the biological samples, and thus a more extensive set of image read-outsenriching the information content for DL image analytics. For example, optofluidic imaging has been employed to effectively probe the mechanical properties of cells, 143,[205][206][207] which are proven biomarkers for different disease conditions such as cancer metastasis, inflammation and cardiovascular diseases. 208,209 Other active microfluidic designs are expected to be increasingly compatible with optofluidic imaging, such as on-chip impedance measurements of microparticles and cells.…”
Section: Scaling Up Throughput By Imaging Flow Cytometry (Ifc)mentioning
confidence: 99%